2013
DOI: 10.1016/j.actbio.2012.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous tissue response and osteogenic performance of calcium phosphate nanoparticle-enriched hydrogels in the tibial medullary cavity of guinea pigs

Abstract: Subcutaneous tissue response and osteogenic performance of calcium phosphate nanoparticle-enriched hydrogels in the tibial medullary cavity of guinea pigs, Acta Biomaterialia (2012), doi: http://dx.doi.org/10. 1016/j.actbio.2012.10.026 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
(42 reference statements)
1
17
0
Order By: Relevance
“…Similar results were also observed with previous HA-based nanoparticles, supporting the bioactivity and osteoinductivity of HA nanoparticles. 1012,14 Compared pure silk particles, higher expression of osteocalcin occurred the silk-HA composite particles without the loading of BMP-2 which suggested that the upregulation of osteocalcin should be due to the HA existence. The controlled release of BMP-2 could also improve the upregulatation of osteocalcin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results were also observed with previous HA-based nanoparticles, supporting the bioactivity and osteoinductivity of HA nanoparticles. 1012,14 Compared pure silk particles, higher expression of osteocalcin occurred the silk-HA composite particles without the loading of BMP-2 which suggested that the upregulation of osteocalcin should be due to the HA existence. The controlled release of BMP-2 could also improve the upregulatation of osteocalcin.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that the presence of HA further improved the biocompatibility of the nanocarriers, which was also revealed in previous studies. 1012,27 Although further investigation was necessary, it was suggested that the organic-inorganic silk-HA composite structures, similar with natural bone microenvironment, provided better niche for the MSCs. Similar results was also found on silk-HA composite scaffolds, where the MSCs proliferated better on the composite scaffolds than on the pure silk scaffolds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both sides of the discs were coated for 15 min at 200 W, resulting in a visually complete layer of titanium roughly 50 nm thick. The elemental composition and distribution of the titanium coating was verified using electron dispersive spectroscopy (EDS), as previously described (Bongio et al, 2013). Briefly, samples were affixed to metal stubs and scanned by a scanning electron microscope (Philips XL30) equipped with an energy dispersive spectrometer (EDAX, Ametek).…”
Section: Methodsmentioning
confidence: 99%
“…Unlike solid scaffolds, hydrogels are fabricated to contain a large amount of water and are characterized by swelling through increasing the water content upon implantation in vivo . This highly hydrated state allows for the free diffusion of oxygen and nutrients into the scaffold, and thus provides an optimum environment for the new bone tissue ingrowth [189193]. Hydrogels are synthesized by crosslinking the branches of hydrophilic polymers using a bridging agent; where the water content depends on the type and concentration of the molecules and the bridging agent [95].…”
Section: Bmp Delivery Systemsmentioning
confidence: 99%